Willingness to pay in alternative improvement scenarios in El Chico National Park, Hidalgo, Mexico - Melo Guerrero, Enrique; Rodríguez Laguna, Rodrigo; Martínez Damián, Miguel Ángel; Hernández Ortiz, Juan; Valenzuela Núñez, Luis Manuel; Ronquillo Gorgúa, Noé (BOSQUE, 2023)
The goal of this research was to economically assess the implementation of an improvement program with four intervention areas in El Chico National Park, Hidalgo, Mexico. This study utilized the methodology of discrete choice experiments, which was conducted with 23 participants using the citizen’s jury approach. By means of a mixed logit model, it was found that the total willingness to pay for the implementation of the improvements in the park was 0.95 USD above the current rate. The most valued area of intervention was regulation of visits, followed by actions to improve forest health and the continuous training of guards. The levels of intervention related to fuel management were not significant. These preferences must be considered by the decision-makers and administrators of the park in order to integrate the opinions of the people who live in this protected natural area and its zone of influence and decide whether they coincide with its conservation goals, in accordance with current environmental legislation.